Chemotherapy for epithelial ovarian, fallopian tube and primary peritoneal cancer. (May 2017) - Webber, Kate; Friedlander, Michael
Abstract : Chemotherapy plays a key role in the management of women with epithelial ovarian, fallopian tube and primary peritoneal cancer (EOC). Platinum- and taxane-based regimens are the standard of care for adjuvant treatment in early-stage EOC and first-line therapy for advanced stage disease. Efforts to define the optimal scheduling, timing and route of administration are ongoing. The majority of women with EOC will develop recurrent disease, and treatment options for these women are depend on the time that has elapsed from first-line therapy. Platinum-based doublet chemotherapy is preferred for women with platinum-sensitive recurrent cancer. In platinum-resistant relapsed EOC, options are much more limited, and careful consideration of symptoms, performance status, anticipated toxicity and quality of life is essential when recommending chemotherapy for these women. Highlights: Platinum/taxane chemotherapies are the first-line treatment of choice. Alternative approaches to scheduling and route of administration are being explored. Ovarian cancer histology influences the response to treatment. Platinum-resistant EOC has poor response to chemotherapy, and QOL is of importance.